2014
DOI: 10.3171/2014.8.spine13897
|View full text |Cite
|
Sign up to set email alerts
|

The role of spinal fusion in the treatment of cervical synovial cysts: a series of 17 cases and meta-analysis

Abstract: Object This study was undertaken to compare surgical outcomes between patients with atlantoaxial versus subaxial cervical synovial cysts (CSCs) and to compare outcomes between patients who underwent decompression alone versus decompression and fusion for the treatment of CSCs. Methods The authors present a series of 17 cases involving patients treated at their institution and report the surgical outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 70 publications
(78 reference statements)
0
19
0
Order By: Relevance
“…81 Furthermore, fusion without cyst evacuation was proven to be effective in cases of cysts arising from the C1/2 joint, 76 which is clearly an exceptional location. However, symptom relief, long-term outcome, and the rate of cyst recurrence with or without fusion are not different in the literature, 14,42,99 despite an increase of mechanical back pain in the nonfusion group reported by Xu et al 100 Information concerning fusion was reported for 1668 patients in the literature, and fusion was performed in 15% during the cyst resection procedure (Supplemental Table 1). The recurrence rate in studies and reports in which 50% or more of the observed cases were initially treated with fusion was nearly equal to that in studies or reports in which less than 50% or no case was fused (2.5% vs 2.2%, p = 0.8).…”
Section: To Fuse or Not To Fusementioning
confidence: 98%
“…81 Furthermore, fusion without cyst evacuation was proven to be effective in cases of cysts arising from the C1/2 joint, 76 which is clearly an exceptional location. However, symptom relief, long-term outcome, and the rate of cyst recurrence with or without fusion are not different in the literature, 14,42,99 despite an increase of mechanical back pain in the nonfusion group reported by Xu et al 100 Information concerning fusion was reported for 1668 patients in the literature, and fusion was performed in 15% during the cyst resection procedure (Supplemental Table 1). The recurrence rate in studies and reports in which 50% or more of the observed cases were initially treated with fusion was nearly equal to that in studies or reports in which less than 50% or no case was fused (2.5% vs 2.2%, p = 0.8).…”
Section: To Fuse or Not To Fusementioning
confidence: 98%
“…Spondylolisthesis of C7–T1 is also a sign of advanced degeneration as seen on our patient. To our knowledge, this is the tenth reported cervical synovial cyst in conjunction with congenital fusion [2] , [11] .…”
Section: Discussionmentioning
confidence: 68%
“…Most commonly, as all types of intraspinal, extradural cysts, [4] subaxial cervical synovial cysts are located at the level C7–T1 [1] , [2] , [3] , [11] . They appear most infrequently on level C2–C3 and C5–C6 [2] , [3] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations